A fine predicament: Conditioning, compliance and consequences in a labeled cash transfer program. (May 2020) - Heinrich, Carolyn J.; Knowles, Matthew T.
Highlights: We compare a conditional cash transfer program arm to a labeled arm that provides only guidance for spending the transfer. About one-third of households in the conditional (CCT) arm received a penalty fine for noncompliance. We find little difference in program outcomes between households in the CCT and labeled (LCT) program arms. Among the poorest households, assignment to the CCT arm was associated with a significant decrease in non-food consumption. Compared to LCTs, CCTs may produce unintended, regressive policy effects for the most vulnerable participants. Abstract: The Kenya Cash Transfer Programme for Orphans and Vulnerable Children (CT-OVC) presents a valuable opportunity to examine the effects of imposing monetary penalties for noncompliance with conditions in cash transfer programs, in contrast to providing only guidance (or "labeling") for cash transfer use. We take advantage of random assignment to a conditional arm within the CT-OVC treatment locations to understand the impact of imposing conditions with penalties on program beneficiaries, as well as how this effect varies by household wealth. Program beneficiaries (orphans and vulnerable children) were expected to visit health facilities for immunizations, growth monitoring and nutrition supplements and to enroll in and attend school. We find little difference in program outcomes between households in the conditional treatment arm compared to those in the treatment arm with labeling only (in which information was provided about these expectations but compliance was not monitored). However, among the poorest CT-OVC beneficiaries, assignment to the conditional arm was associated with penalty fines and a significant decrease in non-food consumption. This suggests that in comparison to labeled cash transfers, conditional cash transfers may produce unintended, regressive policy effects for the most vulnerable participants.